USE OF SUNFLOWER PROTEIN ISOLATE AND BRANS IN THE TECHNOLOGY OF PRODUCTION OF SPORTS BARS - S. Chernenko (Zernovì Produkti ì Kombìkorma)
Modern dietary trends, driven by urbanization and a fast-paced lifestyle, have increased demand for convenient, nutritious products, particularly sports protein bars. These bars serve as a source of protein and brans, making them popular among athletes, office workers, and students. Traditional protein bar formulations use animal- and plant-based protein isolates, such as whey and soy proteins. However, modern requirements for food safety and sustainable production encourage the search for alternatives. A promising ingredient is sunflower protein isolate, derived from sunflower press cake - a byproduct of the oil and fat industry. Ukraine, as one of the world’s leading sunflower producers, has significant potential for utilizing this protein in functional products. Sunflower protein is characterized by a balanced amino acid composition, the absence of antinutritional factors, and hypoallergenic properties, making it a competitive alternative to traditional protein sources. Besides protein, brans play a crucial role in protein bar formulations by supporting digestion, promoting gut microbiota health, reducing glycemic load, and improving texture. Using brans from grain processing byproducts (wheat, oat, and corn brans) and buckwheat hull fiber helps reduce production costs and enhance nutritional value. Studies have shown that oat bran has the highest water-holding capacity (WHC), helping retain moisture in bars, while wheat bran provides a balance between texture stability and softness. Buckwheat hull fiber, rich in antioxidants, increases functional value, whereas corn bran contributes to a denser structure. Market analysis of protein bars in Ukraine revealed formulation differences among manufacturers. Some brands, such as Lipo Bar, offer high-protein bars (up to 40%) with sufficient bran content, while others, such as PowerPro, use lower-cost protein components and high sugar content, reducing nutritional value. This study confirms that sunflower protein isolate is a promising alternative protein source for sports nutrition. However, due to its relatively low lysine content, it is recommended to combine it with lysine-rich proteins such as pea or rice protein. The addition of brans from local sources improves texture, enhances functional properties, and extends product shelf life